The Effect of Subjective Social Status on Quality of Life Among Older Adults: Parallel Mediating Roles of Subjective Health Status and Activity Limitations and the Moderating Effect of Age Group - SEON HEUI KIM (The Korean Gerontological Research Society, 2026)
This study examined the effect of subjective class identification on the quality of life among older adults and investigated the parallel mediating effects of subjective health status and activity limitation, as well as the moderated mediation effect of age group. Data were drawn from the 10th wave (2024) of the Korean Longitudinal Study of Aging (KLoSA), and a total of 4,504 adults aged 65 years and older were analyzed using PROCESS Macro. The results indicated that subjective class identification had a significant positive effect on quality of life. Subjective health status (indirect effect = 1.673) and activity limitation (indirect effect = .388) were found to significantly mediate the relationship between subjective class identification and quality of life. The indirect effect through subjective health status was greater than that through activity limitation, suggesting that health perception plays a more important role in explaining the association between subjective class identification and quality of life. In addition, age group significantly moderated the relationship between activity limitation and quality of life. The negative effect of activity limitation on quality of life became stronger with increasing age. Furthermore, the indirect effect of subjective class identification on quality of life through activity limitation was amplified across age groups, confirming a significant moderated mediation effect (Index of Moderated Mediation = .255). These findings highlight the importance of subjective class identification in shaping the quality of life of older adults and demonstrate the distinct roles of subjective health status and activity limitation as parallel mediators. The study also suggests the need to recognize heterogeneity within the older population and to develop welfare policies and intervention strategies according to age groups.